AN INVESTIGATION INTO MOTIVATIONAL FACTORS THAT INFLUENCING FOREIGN TOURISTS’ TO VISIT JORDAN. PUSH AND PULL FACTORS - BASHAR, A. Alhaj Mohammad; ABDELNASER, Omran (Journal of Environmental Management and Tourism; Vol 2 No 1 (2011): JEMT Volume II Issue 1(3) Summer 2011, 2011)
Tourism sector in the Middle East which has undergone and rapid development has generated foreign exchange and diversities the regional economies. In fact, World Tourism Organization has recognized this area as one of the fastest growing in the world. Despite the growth, however, in terms of tourism research, the Middle East region receives limited attraction. In Jordan, in particular, there are different types of tourism such as archaeological, cultural, historical, religious, adventure, and eco-tourism. While motivations are critical to understanding travel behvaiour, little information has been documented about travel motivations to Jerash city in Jordan. What little information there is, has most often been used to determine destination quality or overall tourist satisfaction rather than identifying specific motivation dimensions. Thus, this paper attempted to discuss the common travel motives of foreign tourists’ to Jerash city in Jordan. In more broad sense, it is purposing to analyze what are the travel motivations that influence those tourists to visit such place. Data were collected from 58 tourists who had traveled to Jordan through questionnaires. Results have shown that there are many push and pull factors that motivated foreign tourist to visit Jordan. One of these push motivational factors were “Getting a change from a busy job” and “Indulging in luxury” while pull motivational factor was “personal safety”.